Web-based test paper generation system - Tran, Trung Kien (2014)
Mathematics is an important subject that can be applied to many different fields of our daily life. In Mathematics course, students usually tackled the subject through textbooks, past year papers, and assessment books. However, with the rapid growth of the Internet and mobile devices, Web-based education has become a ubiquitous learning platform in many schools to provide student materials through freely accessible educational websites. The objective of this project is to tackle the two problems faced in an online assessment system for Additional Mathematic subject: Past Year Papers Analysis and Online Test Paper Generation.